Acamprosate and Baclofen were Not Effective in the Treatment of Pathological Gambling: Preliminary Blind Rater Comparison Study - Dannon, Pinhas N. (Frontiers in Psychiatry, 2011)
Objectives: Pathological gambling (PG) is a highly prevalent and disabling impulse control disorder. A range of psychopharmacological options are available for the treatment of PG, including selective serotonin reuptake inhibitors (SSRI), opioid receptor antagonists, anti-addiction drugs and mood stabilizers. In our preliminary study, we examined the efficacy of two anti-addiction drugs, Baclofen and Acamprosate, in the treatment of PG. Materials & Methods: 17 male gamblers were randomly divided into two groups. Each group received one of the two drugs without being blind to treatment. All patients underwent a comprehensive psychiatric diagnostic evaluation and completed a series of semi-structured interviews. During the six months of study, monthly evaluations were carried out to assess improvement and relapses. Relapse was defined as recurrent gambling behavior. Results: None of the 17 patients reached the six months abstinence. One patient receiving Baclofen sustained abstinence for 4 months. 14 patients succeeded in sustaining abstinence for 1-3 months. 2 patients stopped attending monthly evaluations. Conclusion: Baclofen and Acamprosate did not prove efficient in treating pathological gamblers.